Comparative Study of Maceration and Ultrasonic Techniques in Coffee Oil Extraction Based on Energy Evaluation and Mass Transfer Value - Mustikaningrum, Mega; Yulianto, Mohamad Endy; Prasakti, Laras (CHEESA: Chemical Engineering Research Articles, 2024)
Coffee is a significant commodity trend, with numerous coffee shops rapidly established in Indonesia. The development of this industry has led to an increased discharge of coffee grounds into the environment. The discarded grounds contain oil which can be optimized using various methods and serve as a raw material for biodiesel. Therefore, this study aimed to compare the maceration and ultrasonic methods of extracting coffee grounds. The comparison focused on yield, mass transfer value (diffusivity), and extraction speed constant based on the proposed mathematical model. The results showed a yield of 12.1% and 16%, for the maceration and ultrasonic methods, respectively. Diffusivity value was registered at 9.99 x 10-11 m2/min and 9.8 x 10-10 m2/min, while extraction speed constant values were discovered to be 0.2 m/min and 1.798 m/min, respectively. Additionally, the energy evaluation of ultrasonic extraction produced a Gibbs energy value of -3765.72 Joules.